2019
DOI: 10.1186/s13148-019-0765-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined genetic mutations and DNA-methylated genes as biomarkers for endometrial cancer detection from cervical scrapings

Abstract: Background: Endometrial cancer is a common gynecologic cancer. Noninvasive molecular biomarkers for triage of high-risk patients for invasive procedures are needed. Based on the success of cytological Pap smear screening, cervical scrapings are a good source of DNA for molecular testing. In addition to genetic lesions, DNA methylation is a promising biomarker. We assessed the usefulness of combining genetic and epigenetic biomarkers from cervical scrapings to detect endometrial carcinomas. Methods: We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 41 publications
5
37
0
Order By: Relevance
“…Heart and neural crest derivatives expressed 2 is a transcriptional factor involved in the maintaining of endometrial function ( Kato et al, 2019 ). The methylation and silence of HAND2 contributed to the high risk of EC ( Liew et al, 2019 ; Multinu et al, 2020 ). Based on the immunoprecipitation and pull-down assay, one study also pointed out that HAND2 directly interacted with the amino-terminus of ER-α, resulted in inhibition of the transcriptional expression of it ( Fukuda et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heart and neural crest derivatives expressed 2 is a transcriptional factor involved in the maintaining of endometrial function ( Kato et al, 2019 ). The methylation and silence of HAND2 contributed to the high risk of EC ( Liew et al, 2019 ; Multinu et al, 2020 ). Based on the immunoprecipitation and pull-down assay, one study also pointed out that HAND2 directly interacted with the amino-terminus of ER-α, resulted in inhibition of the transcriptional expression of it ( Fukuda et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they demonstrated that a combination of the analysis of copy number, DNA methylation, and gene mutation improved sensitivity (92%). In another study, combining methylation patterns in several genes ( BHLHE22 , CDO1 , TBX5 , and HAND2 ) with mutations in PTEN and TP53 led to an endometrial cancer diagnosis with a sensitivity of 91.3% and a specificity of 42% [ 58 ].…”
Section: Mechanisms Of Carcinogenesis and Cancer Progression Involmentioning
confidence: 99%
“…Bhlhe22 and Bhlhe23 in turn, are among those that were up-regulated the most in mice during telencephalon development. In humans, Bhlhe22 has been identified as a highly methylated gene in endometrial cancer with potential epigenetic biomarkers in cervical scrapings (Liew et al, 2019), while Bhlhe23 has been linked to mammalian retinal development (Woods et al, 2018).…”
Section: Differential Expression Of Igs In Telencephalon Development Key Genes For Wnt Signalingmentioning
confidence: 99%